2020
DOI: 10.1101/2020.07.29.20164699
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Recurrent Varies with Different Combinatorial Medical Treatments Determined by Machine Learning Approaches

Abstract: Various medical treatments for COVID-19 are attempted. After patients are discharged, SARS-CoV-2 recurring cases are reported and the recurrence could profoundly impact patient healthcare and social economics. To date, no data on the effects of medical treatments on recurrence has been published. We analyzed the treatment data of combinations of ten different drugs for the recurring cases in a single medical center, Shenzhen, China. A total of 417 patients were considered and 414 of them were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Patients with positive NP swab RT-PCR test results after an average of 21 days recurring intervals showed that 19.4% had a second experienced and 3.2% had a third recurrence after a mean interval of 9 and 8 days, commonly. After discharge, the average length of viral shedding at 1st was 7 days, 2nd was 5 days and 3rd was 7 days [23]. When compared with the first admission, patients who were redetectable as positive had moderate clinical symptoms, decreased viral loads, less length of stay, and enhanced lung status upon readmission.…”
Section: Discussionmentioning
confidence: 95%
“…Patients with positive NP swab RT-PCR test results after an average of 21 days recurring intervals showed that 19.4% had a second experienced and 3.2% had a third recurrence after a mean interval of 9 and 8 days, commonly. After discharge, the average length of viral shedding at 1st was 7 days, 2nd was 5 days and 3rd was 7 days [23]. When compared with the first admission, patients who were redetectable as positive had moderate clinical symptoms, decreased viral loads, less length of stay, and enhanced lung status upon readmission.…”
Section: Discussionmentioning
confidence: 95%